a) 216: ( 2 – x ) mũ 3 = 2 mũ 3 b) ( 2x mũ 3 + 12 ) – ( x mũ 3 + 5 ) = 15 c) ( 4 + 3x mũ 2 ) – ( x mũ 2 – 1 ) = 7

Question

a) 216: ( 2 – x ) mũ 3 = 2 mũ 3 b) ( 2x mũ 3 + 12 ) – ( x mũ 3 + 5 ) = 15 c) ( 4 + 3x mũ 2 ) – ( x mũ 2 – 1 ) = 7

in progress 0
Elliana 6 tháng 2021-07-08T23:39:17+00:00 2 Answers 11 views 0

Answers ( )

    0
    2021-07-08T23:40:26+00:00

    `a)216:(2−x)^3=23`

    `⇒216:(2−x)^3=8`

    `⇒(2−x)^3=27`

    `⇒(2−x)^3=3^3`

    `⇒2−x=3`

    `⇒x=−1`

    `b) (2x^3+12)-(x^3+5)=15`

    `=> 2x^3+12-x^3-5=15`

    `=> x^3+7=15`

    `=> x^3=15-7=8`

    `=> x^3=2^3`

    `=> x=2`

    `c) (4+3x^2)-(x^2-1)=7`

    `=> 4+3x^2-x^2+1=7`

    `=> 5+2x^2=7`

    `=> 2x^2=7-5=2`

    `=> x^2=1`

    `=> x=±1`

     

    0
    2021-07-08T23:40:28+00:00

    Đáp án:

     b. x=3

    Giải thích các bước giải:

    \(\begin{array}{l}
    a.DK:x \ne 2\\
    216:{\left( {2 – x} \right)^3} = {2^3}\\
     \to 216:{\left( {2 – x} \right)^3} = 8\\
     \to {\left( {2 – x} \right)^3} = 27\\
     \to {\left( {2 – x} \right)^3} = {3^3}\\
     \to 2 – x = 3\\
     \to x =  – 1\\
    b.\left( {2{x^3} + 12} \right) – \left( {{x^3} + 5} \right) = 15\\
     \to {x^3} + 7 = 15\\
     \to {x^3} = 8\\
     \to {x^3} = {2^3}\\
     \to x = 3\\
    c.4 + 3{x^2} – {x^2} + 1 = 7\\
     \to 2{x^2} + 5 = 7\\
     \to 2{x^2} = 2\\
     \to {x^2} = 1\\
     \to \left[ \begin{array}{l}
    x = 1\\
    x =  – 1
    \end{array} \right.
    \end{array}\)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )